Brand equity, brand loyalty, and customer satisfaction: Case study on Nike - Andika Putra Zarfandi; Astra Prima Budiarti (Universitas Negeri Padang, 2022)
This study aims to prove and analyze the effect of brand equity on brand loyalty with customer satisfaction as an intervening variable for Nike shoe users in Pekanbaru City. In this study, the samples were several users of Nike brand sports shoes in Pekanbaru City. In this study, the research variables used can be grouped into three, namely endogenous variables, namely brand loyalty. The two exogenous variables are brand equity, while the intervening variable is customer satisfaction The data analysis method used quantitative analysis is carried out using Structural Equation Model (SEM) which is processed using Smart PLS assistance. Based on the results of hypothesis testing, it was found that Brand equity had a positive and significant effect on brand loyalty of Nike shoe users in Pekanbaru City. Testing the second hypothesis found Brand equity on customer satisfaction in Nike brand shoes users in Pekanbaru. In testing the third hypothesis, it was found that customer satisfaction has a positive and significant effect on brand loyalty to Nike brand shoe users in Pekanbaru City